What Are Some Best Practices for Internal Corrosion Control?. Issue 11 (1st November 2017) - ,
Abstract : Throughout the last century, lead service lines were used extensively to connect homes to community water systems. Corrosive water can cause lead and other metals to leach from pipes and fixtures into the water we consume. This is what occurred in Flint, Mich., in 2015, and threatens to occur elsewhere when water isn't treated properly.